PENGARUH STRUKTUR PASAR, KOMPETISI, DIVERSIFIKASI, DAN RISIKO KREDIT TERHADAP PROFITABILITAS BANK DENGAN BANK SIZE SEBAGAI VARIABEL KONTROL (STUDI PADA BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Putra, Aditya Mahendra; Pangestuti, Irene Rini Demi (Faculty of Economics and Business Diponegoro University, 2019)
The aims of this research was to examine the effect of market structure (market share,) competition (lerner index), diversification (herfindahl-hirschman index), and credit risk (non performing loans) on Return on Asset (ROA) as a measure of profitability. Firm size is added as control variable on this research. This research used secondary data with population consist of 44 banking listed in Indonesia Stock Exchange in the period of 2012-2016. The purposive sampling method was used in selecting the research sample and 26 banking are chosen to being sample on this research. This research used multiple regression technique for measure the statistic analysis. The result of this research shows that market structure, competition and diversification has a positive significant effect on profitability, but credit risk has a negatif significant effect on profitability.